2020
DOI: 10.1186/s12882-020-02097-w
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation from living donor with monolateral renal artery fibromuscular dysplasia using a cryopreserved iliac graft for arterial reconstruction: a case report and review of the literature

Abstract: Background Aging and mortality of patients on waiting lists for kidney transplantation have increased, as a result of the shortage of organs available all over the world. Living donor grafts represent a significant source to maintain the donor pool, and resorting successfully to allografts with arterial disease has become a necessity. The incidence of renal artery fibromuscular dysplasia (FMD) in potential living renal donors is reported to be 2–6%, and up to 4% of them present concurrent extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Although there are few reports of back-table EBPK reconstruction and transplantation with good graft function previously published [ 7 , 25 27 ], all these reports agree on the crucial role of using a meticulous technique during the vascular reconstruction [ 7 , 25 27 ], which, in the light of the results obtained in this case, we also recognize as essential.…”
Section: Discussionsupporting
confidence: 74%
“…Although there are few reports of back-table EBPK reconstruction and transplantation with good graft function previously published [ 7 , 25 27 ], all these reports agree on the crucial role of using a meticulous technique during the vascular reconstruction [ 7 , 25 27 ], which, in the light of the results obtained in this case, we also recognize as essential.…”
Section: Discussionsupporting
confidence: 74%
“…19,20 In the transplant setting, there has been documented use in solid organ transplants, with several studies demonstrating its use in portal vein reconstruction, cryopreserved iliac artery for renal artery and vein reconstruction, and other reports. [21][22][23][24] A more recent study showed the successful use of cryopreserved allografts in renal vessel extension in living donor kidney transplants without late vascular complications. 25 Despite these studies, a major concern is that because cryopreservation preserves living cells, donor endothelium is subject to both cell-and antibody-mediated rejection, [26][27][28][29] which may contribute to a high failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, renal vessels from living donor kidney allografts are relatively shorter than those from deceased donors; therefore, injury to these vessels often pose a serious challenge. Cryopreserved vascular allografts can be used for renal vascular reconstruction in cases of renal arterial abnormalities in allograft kidneys [ 10 ]. However, it is only to be used for cases in which the abnormal vasculature in the donor’s kidney is diagnosed before LDKT.…”
Section: Discussionmentioning
confidence: 99%